The Fate of Patients Who Started Hemodialysis during Childhood or Adolescence: Results of an Interregional Moroccan Survey. (10th December 2014) - Souilmi, F. Z.; Sqalli Houssaini, T.; EL Bardai, G.; Kabbali, N.; Arrayhani, M.; Hida, M.
Abstract : Hemodialysis is the most used renal replacement therapy for children in Morocco. The objective of this study was to determine the prevalence of patients who started hemodialysis in childhood and study their characteristics and specificities of their care. For this we conducted a multicentric descriptive cross-sectional study of all chronic hemodialysis patients who started dialysis in pediatric age, in hemodialysis centers in four of the sixteen regions of Morocco. We collected 2066 patients undergoing dialysis in 39 hemodialysis centers; from these, only 72 patients (3.48%) started hemodialysis in childhood. The average age of patients was 20.64 ± 6.5 years with a sex ratio of 1.9. Duration of dialysis was 78.2 ± 56 months. The cause of end stage renal disease was urological abnormalities in 18% of cases and glomerulopathy in 12.5% of cases; however, it remains unknown in half of the patients. Over 18 years, 74% of patients are without profession, it is active in 13% of cases, and pursuing studies are only in 13% of cases. Patients under 5 years and those with a low weight are rarely taken care of in chronic hemodialysis with little individualization of prescription. Greater attention should be paid to renal transplantation that is desired by the majority of these patients (92%).